1991
DOI: 10.1007/bf01799628
|View full text |Cite
|
Sign up to set email alerts
|

Gene analysis of mennonite maple syrup urine disease kindred using primer‐specified restriction map modification

Abstract: Maple syrup urine disease (MSUD) is an autosomal recessive inherited disease due to a deficiency of any of the subunits, E1 alpha, E1 beta or E2, of the branched-chain alpha-ketoacid dehydrogenase complex (BCKDH). A large Mennonite kindred of MSUD has been studied in Pennsylvania, USA. In the present investigation, genomes from 70 members, including 12 patients belonging to eight different Mennonite MSUD pedigrees, were examined for possible abnormalities in the E1 alpha gene of BCKDH, by primer-specified rest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1994
1994
2015
2015

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Only one mutation is found with an increased frequency, the 1325T→A transversion that results in a Y393N substitution in E1α. This is the founder mutation responsible for the high incidence of MSUD (1/176) in the Mennonite population (76,79,80). It has been suggested that this mutation may also be found with a high frequency in the general population (81).…”
Section: Molecular Genetics Of Bckdmentioning
confidence: 99%
“…Only one mutation is found with an increased frequency, the 1325T→A transversion that results in a Y393N substitution in E1α. This is the founder mutation responsible for the high incidence of MSUD (1/176) in the Mennonite population (76,79,80). It has been suggested that this mutation may also be found with a high frequency in the general population (81).…”
Section: Molecular Genetics Of Bckdmentioning
confidence: 99%
“…We have investigated the molecular basis of maple syrup urine disease in Italy by examining genomic DNA from 10 patients and their family members for five previously described mutations in the gene encoding the BCKDH complex. The T to A transversion resulting in a Tyr---~ Asp change at position 394 (Y393N) in the mature EI~ subunit was the first mutation described in BCKDH-deficient patients (Zhang et al 1989;Matsuda et al 1990;Fisher et al 1991a) (Mitsubuchi et al 1992). This mutation was identified in a compound heterozygote of non-Mennonite ethnic background (Zhang et al 1989).…”
Section: Discussionmentioning
confidence: 99%
“…Thirteen molecular defects have been identified to date in BCKDHdeficient patients. The T to A transversion causing a Tyr to Asp change at codon 393 in the E1~ protein has been identified independently by several groups (Zhang et al 1989;Matsuda et al 1990;Fisher et al 1991a), and then recognized as the only MSUD mutation in the highly inbred Mennonite population (Mitsubuchi et al 1992). An 11 bp deletion in the region encoding the mitochondrial targeting, leader peptide of the EI~ subunit was found in three Japanese siblings of consanguinous parents .…”
mentioning
confidence: 96%
“…The second step is an oxidative decarboxylation catalyzed by the branched chain α-keto acid decarboxylase complex (BCKDC). These two enzymes associate as a supramolecular complex effecting effi cient channelling of substrates and control over the initial step of BCAA oxidation [ 10 ]. However this mutation has also been found in non-Mennonite patients not all of whom share common Mennonite haplotypes, suggesting the occurrence of the defect in these families is due to either pre-Mennonite or de novo events [ 11 ].…”
Section: Geneticsmentioning
confidence: 98%